2015
DOI: 10.1021/acsnano.5b03763
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Capacitive Deionization Disinfection of Water with Graphene Oxide-graft-Quaternized Chitosan Nanohybrid Electrode Coating

Abstract: Water disinfection materials should ideally be broad-spectrum-active, nonleachable, and noncontaminating to the liquid needing sterilization. Herein, we demonstrate a high-performance capacitive deionization disinfection (CDID) electrode made by coating an activated carbon (AC) electrode with cationic nanohybrids of graphene oxide-graft-quaternized chitosan (GO-QC). Our GO-QC/AC CDID electrode can achieve at least 99.9999% killing (i.e., 6 log reduction) of Escherichia coli in water flowing continuously throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 62 publications
(94 reference statements)
0
45
0
Order By: Relevance
“…The hemolytic effect of depolymerases to erythrocytes was performed using previously described methods with minor modifications (Wang et al, 2015). The separated erythrocytes were washed and diluted to a concentration of 5% (v/v) with PBS.…”
Section: Hemolysis Assaymentioning
confidence: 99%
“…The hemolytic effect of depolymerases to erythrocytes was performed using previously described methods with minor modifications (Wang et al, 2015). The separated erythrocytes were washed and diluted to a concentration of 5% (v/v) with PBS.…”
Section: Hemolysis Assaymentioning
confidence: 99%
“…Srikanth et al [201] fabricated Ag/Ag2O core/shell and Ag/Ag2O decorated multi-layered graphene (MLG) nanostructures with excellent adsorption capabilities to remove As(III) from water, as well as high antimicrobial ability against E. coli and S. aureus. Wang et al [202] reported an activated carbon (AC) electrode coated with graphene oxide-graft-quaternized chitosan (GO-QC) through capacitive deionization disinfection (CDID). It was found that GO-QC/AC CDID electrode could kill at least 99.9999% of E. coli and be easily regenerated in continuous water through the CDID cell, but showed no observable contamination to the water.…”
Section: Water Disinfectionmentioning
confidence: 99%
“…Graphene oxide is attractive as nano filler because of its high aspect ratio and its ease of functionalization with the hydrophilic polymers. GO nanosheets can be easily dispersed in water due to the presence of hydroxyl, carbonyl, epoxy, and carboxylic groups [12][13][14][15]. The high aspect ratio increases the path length molecules have to travel due to an increase in tortuosity.…”
Section: Introductionmentioning
confidence: 99%